Adenoid Cystic Carcinoma of Nasal Cavity: A Rare Case Report - Nishal, Arpita J.; Patel, Mubin; Shahu, Neha S. (Annals of Pathology and Laboratory Medicine, 2020)
Adenoid cystic carcinoma (ACC) was first described by billroth in 1856. It is common in minor salivary glands around the mouth, uncommon in parotids and in Nose and paranasal sinuses. Sinonasal ACC accounts for 10-25% of all head and neck ACC. We are reporting a case of nasal cavity adenoid cystic carcinoma in a 70 year old male patient who was presented with bilateral nasal block, nasal bleeding and loss of vision. On examination polypoidal growth was present in bilateral nasal cavity. Biopsy was taken and sent for histopathological examination. Histopathological findings were suggestive of adenoid cystic carcinoma of nasal cavity. ACC is a slow-growing but highly malignant neoplasm with a remarkable capacity for recurrence. They show no sex predilection and may involve patients of any age, although they usually present in middle-aged or older patients. It has a high risk of recurrence and distant metastasis. Features of diagnostic and therapeutic evaluation are described here with.